Psychological and physiological colour impacts on Malay students in the university hostel environment / Nurlelawati Ab. Jalil - Ab. Jalil, Nurlelawati (Institute of Graduate Studies, UiTM, 2017)
Colour is an environmental stimulus that exerts an influence on human beings in a multitude of ways. The colour effect has been abundantly unequivocally demonstrated in previous research on the integration of multimodal approaches, such as from the psychological, performance and non-performance and preferences assessments. Nevertheless, little research has been conducted locally on the university students with the integration of physiological assessment and consideration of subjects’ living ecology, this being particularly true in the field of design. The fact that no specific colour scheme recommended for the interior of public buildings and double standard perceptions of the importance of visual stimulations are contributing to the monotonous looks at most hostel rooms in public universities. The condition becomes a norm to the students although numerous of research has posited the view that environmental stimuli are correlated with better performances and engagements while the existing white environment contributes to salient negative implications. Worse, inappropriate colours could cause low performances; indirectly affecting moods, dysphoria or depression and health problems among others. In this regards, physiology is another option in understanding the nature of human’s responses to their environments and, in this context, the coloured environment. This is because studies have postulated that colours are detectable in other modality, such as through parasympathetic activities and sympathetic activities, in the human autonomic nervous system (ANS)…